Penerapan Metode Kuantitatif untuk Mengetahui Peningkatan Kepuasan Customer Pada E-Commerce Tokopedia PT Lerys Pet - Yuliana Trisna; Eva Zuraidah (Bulletin of Computer Science Research, 2022)
The purpose of this study was to determine the factors that influence the satisfaction of Tokopedia customers of PT Lerys Pet and to analyze the obstacles and how to overcome them. Especially with regard to the problems that occurred at PT Lerys Pet, namely customer ratings and opinions which greatly affect the rating on E-Commerce Tokopedia PT Lerys Pet, this negative review can tarnish the store's good name and lose trust. If this happens, it shows customer dissatisfaction with the store. So low sales cause small income, and low ratings in E-Commerce thereby reducing customer trust and satisfaction for shopping. This research was conducted by examining 4 variables including price, trustworthiness, product quality, and purchasing decisions. The research uses quantitative methods with data collection techniques carried out by literature studies and distributing questionnaires. While the data analysis technique is done by testing the validity and reliability test. Based on the results of the study, it was found that the validity test of the t arithmetic value of each variable was greater than t table (t arithmetic > t table) thus the data was declared valid with the lowest validity value of 3.410 and the highest 4.765. And the reliability test results Cronbach's Alpha value of 0.875 is greater than 0.70 with a total of 11. Because Cronbach's Alpha 0.875> 0.70 then the data is declared reliable.